Ocular gamut of neurofibromatosis type 1 - Prathibha Shanthaveerappa; Nithisha Tegginamatha; Neethu Narayan Rao; Suyog Ajjampur Suryaprakash (Kerala Journal of Ophthalmology, 2023)
Background: Neurofibromatosis type 1 (NF1) is a multi-system autosomal dominant disorder affecting 1 in 3000 individuals. The diagnostic criteria of NF1 includes ocular manifestations. Objective: To study the ophthalmic manifestations of neurofibromatosis type 1 and evaluate complications, if any. Methodology: A total of 30 eyes of 15 neurofibromatosis cases presenting to the ophthalmology outpatient department (OPD) underwent a detailed ocular examination, and clinical manifestations in each case were analyzed. Results: Lisch nodules were the most common presentation. Twenty-eight eyes of 14 patients had bilateral and one had unilateral presentation. Six eyes of three patients had ectropion uveae, one eye had plexiform neurofibroma, and one eye had pulsatile proptosis with absence of lesser wing of sphenoid. Other manifestations seen were optic nerve glioma, secondary optic atrophy, closed angles with raised intraocular pressure (IOP), medullated nerve fiber and retinal pigment epithelium (RPE) atrophic changes. Conclusion: This case series represents a spectrum of ocular manifestations of NF1 and highlights the importance of ocular examination and regular follow-up in these patients.